Chaos and Unpredictability in Social Thought: General Considerations and Perspectives - Tsekeris, Charalambos (Sociologija. Mintis ir veiksmas, 2010)
This paper attempts to offer a comprehensive and critical overview of the crucial role played by chaos and unpredictability within contemporary social thought. It briefly highlights the relevant theoretical and methodological contributions and developments, as well as the largely useful perspectives emerging from the systematic study of chaos. It is argued that chaos and unpredictability should be responsibly acknowledged, embraced and celebrated as both essential features of human societies and unlimited sources of critical possibilities. Eventually, it is very clear that a kind of guided self-organisation (in social or economic organisations and in human societies) is much better than classical Promethean manipulation and control.